Neskončna struna s točkasto maso - Gašperin, Jaša (Matrika, 2020)
In this article, a large-enough/infinite string with attached point mass will be studied. A spring is attached to the point mass and to static surface. At some time t = 0 our system is excited when a point mass receives velocity ?$v_0$?. The string is shear free and inextensible. Velocity ?$v_0$? will be small enough that the known wave equation ?$\ddot{y} -c^2 y''= 0$? is applicable.
Keywords: infinite string; matematična fizika; mathematical physics; neskončna struna; nihanje; vibration